“Face to face” Learning from others in Facebook Groups - Sandry, Eleanor (Digital Culture & Education, 2014)
This paper extends Emmanuel Levinas’ articulation of “the face to face” encounter (1969, p. 79-81) to suggest that students and teachers can be brought into an ethical proximity created by the media they share and discuss online in Facebook. In Levinas’ terms, a ‘face’ is not simply a physical face. Instead, the Levinasian face encapsulates all the ways that one person is able to reveal aspects of their personality to another. Interactions in Facebook remain “bounded by the impossibility of ever knowing the Other,” as does all communication according to Levinas (Zembylas and Vrasidas, 2005, p. 72). However, while a profile picture may or may not disclose much information about a person, the content posted and shared online (in the form of text, images, videos, likes, etc) reveals aspects of an individual’s personality in a way that encourages responses from others. Facebook can therefore bring people unable to meet in the same physical and temporal location into a proximity created by their online disclosure. In addition, the asymmetry between students and teachers, emphasised in spaces such as lecture theatres, is destabilised in Facebook to provide students and teachers the opportunity to learn from one another’s shared ideas, experiences and understandings.